Peran Orang Tua dalam Meningkatkan Minat Belajar Anak Pada Pembelajaran Daring Di SDN 101 Makale 4 - Hendrik Hendrik (Jurnal Keguruan dan Ilmu Pendidikan, 2022)
Research m aims to project the role of parents in increasing the interest of child learning in online learning this research uses a qualitative method to describe an object in the field, how parents are involved in increasing the interest of child learning in daring- study, myth-collecting techniques using observas, and data analysis methods in the imi research used is data-quality data reductive, data presentation, and plupluses. Based on the results of research shows that the iua people’s role in improving interest in child learning in juvenile detention at SDN 101 Makale 4 Kec. Makale stating that the roe of parents in improving is that some children enjoy doing online learning, without waiting for their parents’ direction to learn yet, there are still people who are less lilely to learn.